THE NAMES OF TRAVELING ROUTESOF THE HISTORICAL UMAN AREA (18th–19th CENTURIES) - Oksana B. Vasylyk (Alfred Nobel University Journal of Philology, 2019)
The purpose of the article is to analyze structural and semantic features of ancient dromonyms and remigationyms of the historical Uman area during their existence, at the beginning of the first fixations in the written texts of 18th–19th centuries to the present day. In the past, the settlements of studied area were connected to each other by the different ways, more or less convenient. All of them at that time were unpaved. By type of traffic, they were divided into postal, trade or caravan, military and grade roads and small paths between villages. The lexemes road and track were used for their names in contrast to the 17th century, when the appellatives way and «hostynets» exist. Most of the names have oikonym origin. The peculiarity of dromonyms of this period was the use of descriptive structures, which took into account such characteristics as size, shape, quality, functionality, location relative to other geographical features. Such onyms consist of a noun in the nominative case and a prepositional structure, which explains the noun by a definition. These structures express the direction and can be the answers to the questions: “Where?”, “Where… from?”. The names-landmarks appear for need to specific location of the new topoobjects relatively to well-known ones. They are formed by a combination of prepositions with nouns in indirect cases. In the microtoponymy system the type of the names “preposition + noun” is quite common. The prepositional structures are typical for microtoponymy of the different regions of Ukraine. But a significant percentage of their usage is in the modern period, as they are active in the oral speech. These names are inefficient for the historical Uman district. In the antiquity the natural connectional routes ran across not only the land, but also the water. Such lexemes as dam and ford are associated with foot or wheel overcoming the shallow water bodies. The names of dams were obtained mainly by their location. The ford was used like the dam. But only one famous of Sinyukhyn Brid was recorded since the 18th century. The analysis of the represented names showed that the investigated dromonyms are predominantly descriptive names that contain prepositional structures. The most characteristic models with the prepositions «with» and «in», that determined the location of new topoobjects relatively to more well-known and significant ones. And the hydrodromonym and the most part of remigationyms are the attributive word combinations organized according to the «adjective + noun» model. The most of onyms disappeared, and some names were renamed during the 20th century.